The face of development aid: volunteers and their hosts in southern Israel. Issue 7 (2nd October 2016) - Gamzu, Shauna; Motzafi-Haller, Pnina
ABSTRACT: The current scholarship on development aid has asserted that a "transformation" of development, one that "puts people first", is presently taking place in the particular form of volunteer aid. In southern Israel, this claim is evident in recent attempts to "strengthen" depressed "development town" communities through a movement that combines Zionist settlement with the volunteer aid of university students. Based on ethnographic work in the development town of Yeruham, this article problematises this claim by investigating the daily encounter of volunteers with members of their multiply marginalised host community. It challenges such claims of "transformation" and exposes the complex social reality of what it means to "develop" and "empower" a population routinely framed as disadvantaged and targeted for aid.